An epidemiologic and clinical description of e-cigarette toxicity. (3rd April 2019) - Hughes, Adrienne; Hendrickson, Robert G.
Abstract: Introduction: E-cigarettes are battery-powered electronic nicotine delivery systems that simulate smoking by vaporizing nicotine-containing solutions. Systematic published data on e-liquid toxicity and exposures are limited to case reports and retrospective studies. Prospectively-collected data on the type of exposure, symptomatology, duration of symptoms, and concentration/flavor of e-fluids has not been published. Methods: This was a prospective observational study over a 42-month period (07/01/2014–12/31/2017). For all calls to a single poison center that involved e-cigarette devices or refill fluid, a data collection instrument was filled out by the specialist in poison information (SPI). Results: Two hundred sixty-five total cases were identified, including 193 children and 72 adults. The majority of both pediatric (72%; 139/193) and adult (61%; n = 44/72) exposures involved e-liquid refill containers or fluid. Fifty-six percent ( n = 108/193) of pediatric exposures involved ingestion of refill liquid. Though children who ingested e-liquid received only a small amount, initial symptoms were evident in 32% ( n = 35/108) of cases. Children who did not ingest or inhale the products were less likely to develop toxicity. Only 2 children who were asymptomatic on initial call became symptomatic on follow-up. Most patients symptoms resolved within 4 hours. Seventy-one specific products/brands were identified with nicotine concentrations ranging from 0 mg/mL to 60 mg/mL with one product containing 3000 mg in a single bottle. A variety of flavors were identified, including several with names that may be attractive to toddlers or adolescents. Discussion: E-cig exposures tend to produce irritant effects from topical exposures and nicotine toxicity from ingestions, as well as some dermal and "sucking" toddler exposures. Conclusion: Exposure to e-cig fluid or device frequently causes mild symptoms and rarely may produce systemic nicotine toxicity.